Study Penerapan Pernyataan Standar Akuntansi Keuangan (PSAK) No. 24 Pada PT Swabina Gatra Gresik - Rusdiyanto, Rusdiyanto; Zaki Al Hamid, Nurhidayah Binti (Fakultas Ekonomi Universitas Gresik, 2019)
Wages are the employee benefits provided by the company to workers for services that have been settled directly to workers, their spouses, children or other dependents. However, on the other hand, wages are also a cost for the company. Therefore, many outsourcing companies are pressing the wages for their workers to minimize the amount of company salary costs, so that the wages given to each worker are not in accordance with applicable government regulations. This prompted researchers to research and analyze wages applied by PT Swabina Gatra Gresik. This research is a qualitative research with descriptive method. PT Swabina Gatra is a national scale outsourcing service provider company. The result of this study is that PT Swabina Gatra Gresik has implemented short-term employee benefits and post-employment benefits based on PSAK No. 24 and also provide minimum basic wages in accordance with the Minimum Wage for the placement city so that they are in accordance with Law No. 13 of 2003 concerning Manpower. Normatively, the provision of wages that are appropriate for the Minimum Wage for Employees (MSEs) does not affect the company's income unless there are problems outside the agreed work contract. It is better if company management continues to innovate so that things do not happen that are not desirable in this era of increasingly fierce competitionÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â Kata Kunci : PSAK No. 24DOI : 10.5281/zenodo.3474592